A CASE REPORT: SOLID-VARIANT ANGIOMATOID FIBROUS HISTIOCYTOMA. (February 2015) - Baccouche, K. Al; Fadia, M.
Abstract : A 16-year-old male presented with a left upper arm cutaneous lesion. Macroscopically, a well circumscribed subcutaneous tumour, with homogenous orange cut surface was identified, which measured 12 mm in maximum dimension. Light microscopy of the excision biopsy revealed a multinodular solid tumour within the deep dermis and subcutis. It showed a proliferation of oval to spindled cells with vesicular nuclei, with indistinct cell borders. Multinucleated and symplastic smudge cells were identified. There was marked nuclear pleomorphism and mitotic figures were readily identified. The tumour had a pseudocapsule and pericapsular cuffing with lymphoid aggregates, some with germinal centres. Immunhistochemically, the tumour cells were positive for EMA, SMA and CD99. Fluorescence in situ hybridization (FISH) confirmed EWSR1 gene rearrangement. Overall, the clinical, histological, immunophenotypic and FISH features were in keeping with a solid-variant of angiomatoid fibrous histiocytoma. Angiomatoid fibrous histiocytoma is a rare soft tissue tumour that is classified in the WHO as an intermediate potential mesenchymal tumour. It usually occurs on the exteremities of children and young adults. The diverse alteration in histomorphology and immunoprofile may pose some diagnostic problem, which can be resolved by performing FISH analysis.